Toxicity assessment and bioaccumulation of heavy metals in red tilapia / Mohammed Abdulridha Jasim Aldoghachi - Mohammed Abdulridha, Jasim Aldoghachi (2016)
The aims of this study are to evaluate the acute toxicity of different exposure concentrations of Cd, Cu, Hg, Mg, Pb, and Zn on survival, histopathological effects and to assess accumulation level in the tissues of muscles, gills and liver of red tilapia Oreochromis sp. As well as to measure heavy metals concentration in aquaculture ponds fish at selected different sites in Malaysia (Serendah, Kampar, Bistari Jaya and Bukit Tinggi). In this work, red tilapia was chosen because it has become a significant food source for human being and is considered as a commercially important fish of the aquacultures in Malaysia. In the method of acute toxicity test, the healthy fingerlings were collected from a commercial aquaculture in Serendah, Selangor Kuala Lumpur, Malaysia. Thereafter, the fish were acclimatized in laboratory; the tilapias were semistatically exposed to different concentrations of heavy metals during 96 hours in order to determine the median lethal concentration (LC50) which was estimated by the probit transformed concentration response curves. The fish were dissected into gills, liver and muscles and then digested by adding 6 ml nitric acid (65 %) and 1ml H2O2 (35%) in microwave oven; the concentration of heavy metals in fish samples was determined by ICP–OES (Perkin Elmer AA Analyst) and mercury analysis was performed by Flameless Atomic Absorption spectrophotometer. Histopathological characteristics and lesions were conducted on gills and liver from fishes which were exposed to sub-lethal concentration 96hLC50 /2 over 96 hours. The digital images were obtained by using a light microscope Nikon type Eclipse E200, equipped with a Dino eye camera Ø30mm. Morphological analysis on gills of experimental fish was carried out and the weight percent mineral contents through the cross-section of gills were quantified by energy dispersive X-ray (EDX) spectroscopy analysis using a Scanning Electron Microscope equipped with EDX. In toxicity assay, the results showed that tilapia fish had a higher sensitivity to Hg and Cu followed by Cd and Zn but poor response to Mg and Pb. Among the tested metals, Mg had a lower impact on fish survival and it was accumulated in higher level. Toxic metals accumulation levels were in the following order: Mg > Zn > Cu > Pb > Cd in all organs. These elements caused severe tissue damage which led to alterations of histopathological aspects represented in proliferation of filamentary epithelium with fusion of adjacent secondary lamellae and an increase in chloride cell density of gills. The liver of tested fish showed disorganization of hepatic cells, hypertrophy of hepatocytes severe degradation of the liver parenchyma, and necrosis. The scanning electron micrographic images gave more details about the effect of the elements on the gills which showed disappearance and fusion of microridges in pavement cells. In addition, EDX microanalyses showed an increase in the weight percentage of element in primary and secondary lamellae of gills in experimental fish. Current study provided useful information and a baseline for future along with continuous studies on the heavy metals concentrations in red tilapia fish of aquaculture ponds. The detected metals concentrations varied significantly (p < 0.05) among different tissues and the lack of significant variation between the tested sites. The heavy metals concentrations were found to be lower than the recommended maximum level allowed in food by Malaysian Food Act 1983 and Food Regulations 1985. These findings confirmed that tilapia fish from all studied aquaculture ponds are safe for human consumption.